Afaquia no corregida en paciente masculino de 57 años. - Naula Alvarado, María Lourdes (2021)
In the following clinical case, an older adult is drawn up, who comes to the consultation subject to the arm of a companion, claims to be 57 years old, having had unsuccessful eye surgery in his right eye (RE) a year ago, presents a cataract in his left eye (OI) and postoperative psychological trauma, with a family history of arterial hypertension and a personal history of type II diabetes mellitus, visual acuity was assessed with a Snellen chart at 20 feet to 10 feet and 3 feet, with the best visual acuity being 3/200 in right eye and left eye does not refer. Unilateral aphakia was diagnosed in his right eye and refraction was performed with positive measurements considering the diopter values of the lens outside the eye of +12.50 diopters. The objective of this case is to assess the uncorrected aphakia in a 57-year-old male patient. Seeking in this way to reintegrate the elderly patient within the social and family system so that they can resume their daily activities as much as possible, and thus, the patient achieves a social, emotional and personal well-being that affects their quality of life, considering that visual loss it causes great suffering both for those who suffer it and for their families. In this clinical case study, subjective refraction: RX was assessed for uncorrected aphakia in the elderly. Esf. OD: + 14.00; OI: Compensation; ADD: 2.00 DP 64. Possible treatments were identified and the best for this case was the device with bifocal ophthalmic technology "Hi-Drop non-lenticular" in organic material for aerial lenses or glasses, leaving their visual acuity with distance correction (AVCCL) 20/20 and his visual acuity with near correction (AVCCC) 0.50 M